Genome-wide genetic analyses highlight MAPK signalling in the pathogenesis of endometriosis - UImari, O; Rahmioglu, N; Nyholt, D; Vincent, K; Missmer, S; Becker, C; Morris, A; Montgomery, G; Zondervan, K (Oxford University Press, 2017)
Study Question Do genome-wide association study (GWAS) data for endometriosis provide insight into novel biological pathways associated with its pathogenesis? Summary Answer GWAS analysis uncovered multiple pathways that are statistically enriched for genetic association signals, analysis of Stage A disease highlighted a novel variant in MAP3K4, while top pathways significantly associated with all endometriosis and Stage A disease included several mitogen-activated protein kinase (MAPK)-related pathways. What is Known Already Endometriosis is a complex disease with an estimated heritability of 50%. To date, GWAS revealed 10 genomic regions associated with endometriosis, explaining <4% of heritability, while half of the heritability is estimated to be due to common risk variants. Pathway analyses combine the evidence of single variants into gene-based measures, leveraging the aggregate effect of variants in genes and uncovering biological pathways involved in disease pathogenesis. Study Design, Size, Duration Pathway analysis was conducted utilizing the International Endogene Consortium GWAS data, comprising 3194 surgically confirmed endometriosis cases and 7060 controls of European ancestry with genotype data imputed up to 1000 Genomes Phase three reference panel. GWAS was performed for all endometriosis cases and for Stage A (revised American Fertility Society (rAFS) I/II, n = 1686) and B (rAFS III/IV, n = 1364) cases separately. The identified significant pathways were compared with pathways previously investigated in the literature through candidate association studies. Participants/Materials, Settings, Methods The most comprehensive biological pathway databases, MSigDB (including BioCarta, KEGG, PID, SA, SIG, ST and GO) and PANTHER were utilized to test for enrichment of genetic variants associated with endometriosis. Statistical enrichment analysis was performed using the MAGENTA (Meta-Analysis Gene-set Enrichment of variaNT Associations) software. Main Results and the Role of Chance The first genome-wide association analysis for Stage A endometriosis revealed a novel locus, rs144240142 (P = 6.45 × 10−8, OR = 1.71, 95% CI = 1.23–2.37), an intronic single-nucleotide polymorphism (SNP) within MAP3K4. This SNP was not associated with Stage B disease (P = 0.086). MAP3K4 was also shown to be differentially expressed in eutopic endometrium between Stage A endometriosis cases and controls (P = 3.8 × 10^−4), but not with Stage B disease (P = 0.26). A total of 14 pathways enriched with genetic endometriosis associations were identified (false discovery rate (FDR)-P < 0.05). The pathways associated with any endometriosis were Grb2-Sos provides linkage to MAPK signaling for integrins pathway (P = 2.8 × 10^−5, FDR-P = 3.0 × 10^−3), Wnt signaling (P = 0.026, FDR-P = 0.026) and p130Cas linkage to MAPK signaling for integrins pathway (P = 6.0 × 10−4, FDR-P = 0.029); with Stage A endometriosis: extracellular signal-regulated kinase (ERK)1 ERK2 MAPK (P = 5.0 × 10^−4, FDR-P = 5.0 × 10^−4) and with Stage B endometriosis: two overlapping pathways that related to extracellular matrix biology—Core matrisome (P = 1.4 × 10^−3, FDR-P = 0.013) and ECM glycoproteins (P = 1.8 × 10^−3, FDR-P = 7.1 × 10^−3). Genes arising from endometriosis candidate gene studies performed to date were enriched for Interleukin signaling pathway (P = 2.3 × 10^−12), Apoptosis signaling pathway (P = 9.7 × 10^−9) and Gonadotropin releasing hormone receptor pathway (P = 1.2 × 10^−6); however, these pathways did not feature in the results based on GWAS data. Limitations, Reasons for Caution The analysis is restricted to (i) variants in/near genes that can be assigned to pathways, excluding intergenic variants; (ii) the gene-based pathway definition as registered in the databases; (iii) women of European ancestry. Wider Implications of the Findings The top ranked pathways associated with overall and Stage A endometriosis in particular involve integrin-mediated MAPK activation and intracellular ERK/MAPK acting downstream in the MAPK cascade, both acting in the control of cell division, gene expression, cell movement and survival. Other top enriched pathways in Stage B disease include ECM glycoprotein pathways important for extracellular structure and biochemical support. The results highlight the need for increased efforts to understand the functional role of these pathways in endometriosis pathogenesis, including the investigation of the biological effects of the genetic variants on downstream molecular processes in tissue relevant to endometriosis. Additionally, our results offer further support for the hypothesis of at least partially distinct causal pathophysiology for minimal/mild (rAFS I/II) vs. moderate/severe (rAFS III/IV) endometriosis.